NEWS TEXT GENRE OF THE BALI TIMES - Johanes Sutomo (Master Program in Linguistics, Diponegoro University, 2014)
This study aims at portraying some aspects of the contextual configuration of Bali Times’s news texts. The study focuses on the communicative purposes, linguistic features and schematic structures of the news text genre. The method used is descriptive, and the approaches are quantitative and qualitative. The results revealed that the news texts could be categorized as the genre of news service. The Generic Structure Potential (GSP) deriving from the selected news texts may accomplish the service. The GSP is a condensed statement and a powerful device that generates a large number of possible actual structures. Penelitian ini dilakukan untuk memotret beberapa aspek dari konfigurasi kontekstual dari teks berita Bali Times. Penelitian ini difokuskan pada tujuan komunikatif, fitur linguistik dan struktur skematik dari genre teks berita. Metode yang digunakan deskriptif, dengan pendekatan kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa teks berita dapat dikategorikan sebagai genre layanan berita. Struktur Generik Potensial yang merupakan derivasi dari teks berita terpilih dimungkinkan mampu memenuhi layanan ini. Struktur ini merupakan pernyataan ringkas dan sebagai perangkat yang hebat yang mampu menggeneralisasi struktur aktual yang memungkinkan dalam jumlah yang besar